Epstein-barr virus and its association with breast cancer / Prof Madya Dr Hjh Zuridah Hj Hassan and Dr Zeenathul Nazariah Allauddin - Hassan, Zuridah (Research Management Institute (RMI), 2010)
Epstein-barr virus (EBV) is widely distributed with 90-95% of adults are seropositive. This virus is spread by intimate contact between susceptible persons and asymptomatic shedders. EBV can be the causative agent of some B and T cell lymphomas, Hodgkin disease, nasopharyngeal carcinoma and also as one of the cofactor in the development of many types of carcinomas including breast cancer. The role of Epstein-barr virus (EBV) in breast cancer is not well documented and reports are very controversial. On the other hand, current belief holds that chromosomal deficiency and translocation, deletion, insertion and point mutation in the p53 tumor suppressor gene (p53 gene) which plays an important role in the regulation of cell growth, differentiation and DNA repair can play a role. Abnormal cell proliferation is thought to be induced by p53 gene deficiency. In human carcinogenesis, p53 mutations are reported in esophageal carcinoma with documented changes in protein expression. There is also evidence that mechanisms other than point mutation may result in p53 protein accumulation and inactivation in a subset of breast cancer. Epidemiologic studies have implicated several lifestyle risk factors: tobacco exposure, alcohol consumption, diet, obesity in esophageal carcinoma. However, the clinical significance and potential applications of these observations in breast cancer remains unclear.